Functional analysis and geometry : Selim Grigorievich Krein centennial - Kuchment, Peter, 1949-; Semenov, E. M. (Evgeniĭ Mikhaĭlovich) (Contemporary mathematics (American Mathematical Society), 2019)
This is the first of two volumes dedicated to the centennial of the distinguished mathematician Selim Grigorievich Krein. The companion volume is Contemporary Mathematics, Volume 734. Krein was a major contributor to functional analysis, operator theory, partial differential equations, fluid dynamics, and other areas, and the author of several influential monographs in these areas. He was a prolific teacher, graduating 83 Ph. D. students. Krein also created and ran, for many years, the annual Voronezh Winter Mathematical Schools, which significantly influenced mathematical life in the former So.